Explaining the nurses' spiritual needs in the oncology department: A qualitative study - Seyed Rohollah Mosavizadeh; Masoud Bahrami; Asieh Maghami-Mehr; Mohammad Torkan; Ladan Mehdipoorkorani (Iranian Journal of Nursing and Midwifery Research, 2024)
Background: It seems that improving the spiritual dimension of cancer patients can play an effective role in their mental and emotional peace. Meanwhile, oncology ward nurses are one of the most important healthcare providers that can help improve patients' relationship with God due to their more interaction and communication with patients. For this reason, this study aimed at explaining nurses' spiritual needs in an oncology ward. Materials and Methods: This study was conducted based on the qualitative content analysis method. The participants included 11 nurses from the oncology ward of Seyed Al Shahada Hospital in Isfahan from 2021 to 2022. A semi-structured interview was administered to determine nurses' spiritual needs. Results: Analysis of 11 interviews conducted with nurses revealed a total of four main codes, 13 sub-codes, and four sub-sub-codes. According to nurses' point of view, their spiritual needs can be classified into four dimensions as follows: communication with God, communication with oneself (intrapersonal communication), communication with others (interpersonal communication), and communication with environment. Administered interviews revealed the role of communication with God with six sub-codes as nurses' most important point of attention. Conclusions: According to nurses' point of view, nurses' spiritual needs were divided into the dimensions of communication with God, communication with oneself, communication with others, and communication with environment. Therefore, it is necessary to simultaneously pay attention to oncology nurses' personal and social aspects to increase their spirituality.